Pengaruh Modernisasi di Turki terhadap Penafsiran Bediuzzaman Said Nursi - Labib Syauqi Akifahadi (Refleksi, 2012)
This paper describes how the influence of modernization that occurred in Turkey on the interpretation of Said Nursi, who focused on the three important points, i.e. the interpretation on science and technology, the relation of religion and state, and on gender relations. First, for Nursi, science has a neutral nature, because it needs to be appreciated, whether it comes from Islam or from the West. Second, Nursi made formulations that nationalism manifested in the form of blind secularization or excessive Westernization is wrong. Two things above, science and nationalism formula must be an integrated harmony with Islamic values and not detached from local cultural roots. Third, the issue of gender equality and the relation of men-women, for Nursi, must be realized with the aim to mutually, harmonious and dynamic life, not in the form of oppressing and to control each other.DOI: 10.15408/ref.v13i2.900